Phytotoxic effects of aqueous extracts of olax subscorpioidea oliv. on seed germination and growth parameters of maize (zea mays l.) (2020)
Phytotoxicity of wild plants is sometimes utilized in the control of weeds. Their effects on crops are however not extensively documented. Effects of aqueous extracts of Olax subscorpioidea Oliv. were thus examined on seeds and seedlings of maize. Two experiments were laid out in complete randomized designs (CRD) and replicated five times. Ten seeds of maize were initially placed in separate petri-dishes and moistened daily with two (2) ml water extracts of different parts of Olax sp. while 2 ml of distilled water served as control. Secondly, maize seedlings growing on top soil in experimental pots were treated with 100 ml of extracts at seven days intervals for eight weeks. Data were collected on number of germinated seeds daily, and lengths of five randomly selected plumules and radicles at 7 days after sowing (DAS). Number of leaves, plant height, root dry weight and shoot dry weight of seedling were measured using standard methods. Analysis of variance and Duncan’s Multiple Range Test were conducted to statistically determine significant means at P=0.05. Mean germination of (0.71±0.00) was observed at 2 DAS and 2.81±0.10 at 7 DAS. Leaf extracts significantly reduced germinability, but significantly increased number of leaves, plant height (26±1.28), root dry weight (10.30±3.24) and shoot dry weight (14.99±2.13). The results showed that Olax subscorpioidea has alloallelopathic (phytotoxic) effects on maize seeds, but stimulated growth of maize seedlings. Its use as a bio-herbicide or growth stimulant in should be well-timed.